2015
DOI: 10.1055/s-0035-1549907
|View full text |Cite
|
Sign up to set email alerts
|

Impfkühlschrank- und Impfstoffmanagement in Hausarztpraxen: Eine repräsentative, Web-basierte Umfrage unter Hausärzten (Keep Cool I)

Abstract: The purpose of this study was to analyse vaccine refrigerator and vaccine management in primary care and to identify physician- and practice-related influencing factors. Adequate cooling of vaccines in a temperature range of 2-8°C is essential to assure vaccine effectiveness. Studies from various countries have demonstrated cooling chain problems. We surveyed general practitioners about the quality of their vaccine refrigerator and vaccine management and aimed at identifying physician- and practice-related inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Also, 20.3% to 52.6% of the practices incorrectly stored vaccines in door shelves [ 12 , 13 , 17 ]. In a 2014 survey among German general practitioners (GP), 16% reported cold chain breaches as error or near error, and only 51% reported to document refrigerator temperatures twice a day as recommended [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, 20.3% to 52.6% of the practices incorrectly stored vaccines in door shelves [ 12 , 13 , 17 ]. In a 2014 survey among German general practitioners (GP), 16% reported cold chain breaches as error or near error, and only 51% reported to document refrigerator temperatures twice a day as recommended [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to a systematic literature review, freezing temperature exposure occurred in approximately 33.3% of refrigerators used for vaccine storage in ten wealthier countries [14]. In our prior cross-sectional questionnaire study, 16% of German general practices self-reported experiencing cold chain breaches either as an error or near-error, and 49% lacked adequate monitoring and documentation [15,16]. The Keep Cool study aims at ensuring optimal vaccine storage conditions: after visual inspections of refrigerators used to store vaccines and a baseline temperature survey of seven days, general practices with temperature violations are offered access to a tailored online learning program [17,18].…”
Section: Introductionmentioning
confidence: 99%